Production Of L-Glutamic Acid As A Function Of Urease Activity By Corynebacterium glutamicum X680 Using Agro-Based Raw Materials: Life Sciences-Microbiology for health care - Subhadeep Ganguly (International Journal of Life Science and Pharma Research, 2022)
Urease catalyzes hydrolysis of urea. The present investigation was undertaken to investigate the urease activity and its optimization during L-glutamic acid fermentation by a biotin auxotroph Corynebacterium glutamicum X680 using urea as the principal nitrogen source. Another interesting part of this study was to investigate the efficiency of this microorganism for utilization of indigenous raw materials (such as hydrolysates of cassava starch, rice bran and wheat bran) as a cheap carbon sources instead of glucose. Among different raw materials, hydrolysate of cassava starch appeared to be the most suitable. However, the production efficiency is significantly less (p<0.01) with cassava starch compared to glucose. When the medium is supplemented with equivalent amount of (10g%) cassava starch hydrolysate, the L-glutamic acid accumulation was reported to be 18.2mg/ml with maximum urease activity (0.18U/mg protein) with pH7 at 300C.Thus, among the different agro-based wastes were examined, cassava starch hydrolysate appeared to be the best alternative of glucose to minimize L- glutamic acid production cost.